Potential land productivity calculation in foothill and mountain area based on GIS and spatial interpolation technology - ZHU Lei; HUANG Jing-feng (浙江大学学报. 农业与生命科学版)
The potential land productivity of study area was calculated with geographical information system (GIS), database including weather, hydrology and soil data based on previous research of other experts. Mechanism methodology was used to calculate potential land productivity, and its spatial distribution was analyzed through classification statistics and classification mapping. For the spatial variation of temperature and precipitation are more evidence in foothill and mountain area of south China, 30 m×30 m cell size was used to calculate potential land productivity, and precipitation and temperature spatial simulation using detailed data of meteordogical and precipitation stations was focused on.